Evaluación de ácidos grasos en las carcasas de cerdos alimentados con sorgo termoprocesado durante el crecimiento y la terminación (Semiárida, 2018)
The growing interest on meat and fat quality has brought the implicit need to know the content and composition of pig carcass fat, due to probable negative impacts on human health. The greatest challenges are the reduction of saturated fatty acids content in meat, mainly palmitic acid, and the increase of mono- and poli-insaturated fatty acids amount. The aim of this study was to determine the composition of fatty acids in depot tissues of pigs at 90 kg of liveweight, fed on different diets, containing sorghum grains processed in different ways, or ground corn. The samples were obtained in vivo from subcutaneous fat, by biopsy. Once the samples were stabilized, the most abundant fatty acid, and the percentage of relative abundance in each sample were determined by a gas chromatography - mass spectrometry (GC - MS) coupling technique. From this experience it could be concluded that the pigs fed on sorghum, independently from its presentation, show carcasses higher in mono- and poli-insaturated fatty acids. Those fed on ground and extruded sorghum had linolenic acid in their carcasses. The diets composed by thermo-processed sorghum showed higher meat quality carcasses
Keywords: Pork fat; Fatty acid composition; Thermo-processed sorghum